Neologisms in the Kabardino-Circassian language (based on linguistic terminology) - Khazhismel Ch. Zhiletezhev; Liana Kh. Zhiletezheva (Кавказология, 2023)
This article examines the process of new linguistic terms emergence in the Kabardino-Circassian language. This work analysed the terms created by the Kabardino-Circassian language’s own linguistic sources. The initiator of the creation of these terms is the scientist-educator Sh.B. Nogmov. The main stage of the linguistic creation, terminological system of the Kabardino-Circassian language, begins in the 30s of the twentieth century. During the research, the author concludes that the founder of the national linguistic terminology is T.M. Borukaev. He is the author of various terms that are successfully used in the Kabardino-Circassian language to this day. In the post-war years, H.U. Elberdov was engaged in creating linguistic terms. He successfully introduced several terms of his own into the language. In the last half century, creating new linguistic terms has practically ceased. The analysis of the literature shows that in the modern Kabardino-Circassian language, there is an unjustified use of many borrowed terms. This problem is a serious disadvantage for researchers in their native language. There are solutions for this situation, proposed by the Doctor of Philology B. Ch. Bizhoev. He created the first dictionary of linguistic terms in the Kabardino-Circassian language, which includes about 1865 terms. Based on the study of the terms, it was found that almost all of them received an accurate and adequate translation into the Kabardino-Circassian language. The relevance of this study lies in the increasing need to study the linguistic terminology of the Kabardino-Circassian language. Descriptive-analytical method, contextual analysis, statistical calculation are used in the work.